Physical, chemical, technological and toxicological characteristics of teiu potato flour (Jatropha elliptica (Pohl) Oken) - Correia Bento, Juliana Aparecida; Neto, Menandes Alves de Souza; Luiz A. M. Bataus, Armando G. Rodriguez; Manoel S. S. Júnior, Márcio Caliari (Emirates Journal of Food and Agriculture, 2019)
Jatropha elliptica (Pohl) Oken, popularly known as teiu potato, is widely used in folk medicine as a purgative and in the treatment of snake bites. There is no scientific data on the physicochemical characterization or anti-nutritional compounds, nor are there any reports on the application of this root in the production of flours for food purposes. Thus, the objective of this work was to contribute with new knowledge concerning the production yield of teiu potato root flour, characterize its physical, chemical and technological properties, and determine its anti-nutritional and toxicological factors. The flour was obtained on three repetitions (batches) and all analyses were carried out in triplicate for each repetition. The flour production yield was 34.29%, and the product obtained was an orange powder with a carbohydrate content of 77.55 g·100 g-1, high contents of total dietary fiber (22.8 g·100 g-1), protein (8.3 g·100 g-1) and ash (3.5 g·100 g-1), and a low lipid (0.8 g·100 g-1) content. The thermogram of the flour showed three endothermic peaks: temperature of gelatinization of the flour starch (77.42 °C); glass transition (106.55 °C) and protein and lipid-amylose complexes (131.77 °C). The flour presented antioxidant potential (89.59% of DPPH discoloration), a high concentration of phenolic compounds (12.67 mg eq gallic acid·100 g-1), nitrates (4.4 g·Kg-1), tannins (5.4 g tannic acid·100 g-1) and trypsin inhibitors (4.3 UTI·mg-1). The teiu potato flour requiring further, more profound studies before being indicated for human nutrition, due to the presence of anti-nutritional factors and the toxicity presented in the test with Artemia salina.